2013
DOI: 10.1089/thy.2012.0451
|View full text |Cite
|
Sign up to set email alerts
|

Remnant Uptake as a Postoperative Oncologic Quality Indicator

Abstract: Background: The purpose of this study was to examine the utility of remnant uptake on postoperative radioiodine scans as an oncologic indicator after thyroidectomy for differentiated thyroid cancer (DTC). Methods: We conducted a retrospective review of patients undergoing total thyroidectomy for DTC and subsequent radioactive iodine (RAI) treatment. Of the eight surgeons included, three were considered high volume, performing at least 20 thyroidectomies per year. Patients with distant metastases at diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 54 publications
3
55
2
Order By: Relevance
“…The threshold number of thyroid procedures that differentiates high-volume from low-volume surgeons varies and studies have found differences at 20, 30, and 100 cases per year. 10,12,13,[17][18][19] However, surgeon volume has only recently been examined for its impact on markers of initial completeness of resection in a study by Schneider et al 19 With today's decreasing use of postoperative I 131 and routine use of highly sensitive testing modalities for surveillance, completeness of initial surgery may be even more critical. The aims of this study are to determine the influence of surgeon volume on (1) the frequency of appropriate initial surgery for DTC and (2) additional quantitative measurements of completeness of resection.…”
mentioning
confidence: 99%
“…The threshold number of thyroid procedures that differentiates high-volume from low-volume surgeons varies and studies have found differences at 20, 30, and 100 cases per year. 10,12,13,[17][18][19] However, surgeon volume has only recently been examined for its impact on markers of initial completeness of resection in a study by Schneider et al 19 With today's decreasing use of postoperative I 131 and routine use of highly sensitive testing modalities for surveillance, completeness of initial surgery may be even more critical. The aims of this study are to determine the influence of surgeon volume on (1) the frequency of appropriate initial surgery for DTC and (2) additional quantitative measurements of completeness of resection.…”
mentioning
confidence: 99%
“…Interestingly, despite the likely more extensive surgical resection by the high-volume surgeons, they also had lower rates of complications, suggesting that a high-volume surgeon can safely perform surgery that is more extensive. 25 This finding suggests that remnant uptake predicts recurrence and assists in judging the quality of the initial surgical management. These results provide surgeons with valuable feedback that may help them to improve their surgical outcomes.…”
Section: Assessing the Adequacy Of Surgical Resectionmentioning
confidence: 93%
“…We previously studied patients with differentiated thyroid cancer (DTC) who underwent total thyroidectomy and then received RAI postoperatively. 25 Eight surgeons were included and were classified as high volume if they performed >20 thyroidectomies per year. We calculated an uptake to dose ratio (UDR) for each patient, which demonstrated that UDR was 10-fold higher in patients who later presented with a recurrence.…”
Section: Assessing the Adequacy Of Surgical Resectionmentioning
confidence: 99%
“…Post-treatment RAI WBS performed 3-10 days after I-131 treatment may assist in the localization of residual disease and delineate the risk of recurrence, as shown in a recent study by Schneider et al [30]. To control for I-131 dose variation, the authors calculated an uptake-to-dose ratio, in which uptake was defined as the percentage of the total I-131 dose administered that was detected within the thyroid bed after adjusting for decay.…”
Section: Radioiodine Dosing and Treatment Proceduresmentioning
confidence: 99%